2007
DOI: 10.1021/es061797i
|View full text |Cite
|
Sign up to set email alerts
|

Air−Water Exchange of Polychlorinated Biphenyls in the Delaware River

Abstract: The air-water exchange of polychlorinated biphenyls (PCBs) often results in net volatilization, which is thought to be the most important loss process for PCBs in many systems. Previous investigations of the air-water exchange of PCBs have been hampered by difficulties in treatment of the uncertainty in the calculation of air/water fugacity ratios. This work presents a new framework for the treatment of uncertainty, where uncertainty in physical constants is handled differently from random measurement uncertai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 27 publications
3
54
1
Order By: Relevance
“…However, CB-209 was comprised <1% of the PCBs in most of the commercial Aroclors except Aroclor 1268 (Kannan et al, 1997). Rowe et al (2007) observed higher level of CB-209 in the suspended solids of Delaware River, and one possible source is a titanium dioxide purification plant that is located on the lower Delaware. In the present study, field investigation indicated S2 and S3 sites could be affected by some industrial cities, e.g., Lvliang City, Yulin City and Baotou City, where coal chemical industry, metallurgy, rareearth (RE), manufacturing were extensively developed.…”
Section: Pca Analysismentioning
confidence: 89%
“…However, CB-209 was comprised <1% of the PCBs in most of the commercial Aroclors except Aroclor 1268 (Kannan et al, 1997). Rowe et al (2007) observed higher level of CB-209 in the suspended solids of Delaware River, and one possible source is a titanium dioxide purification plant that is located on the lower Delaware. In the present study, field investigation indicated S2 and S3 sites could be affected by some industrial cities, e.g., Lvliang City, Yulin City and Baotou City, where coal chemical industry, metallurgy, rareearth (RE), manufacturing were extensively developed.…”
Section: Pca Analysismentioning
confidence: 89%
“…In New York-New Jersey Harbor, higher dissolved-phase PCB concentrations were measured with a maximum value of 4160 pg L − 1 (Totten et al, 2001). In Delaware River, the highest value of dissolved and particle phase PCB concentrations were 1700 and 4900 pg L − 1 , respectively (Rowe et al, 2007).…”
Section: Water Concentrationsmentioning
confidence: 98%
“…This corresponds with the heavy industrial presence in North China compared to South China. The levels of PCBs in the Haihe, Huaihe and Tonghui Rivers were higher than those in the Houston Ship Channel, USA (0.49e12.5 ng/L) (Howell et al, 2008), Ebro River in Spain (43.2e108 ng/L) (Gómez-Gutiérrez et al, 2006), Mississippi River (22.2e163 ng/L) and Delaware River (0.42e1.65 ng/L) (Rowe et al, 2007) (Table S2), suggesting that PCB contamination in these rivers are at the high end of the global range.…”
Section: Riversmentioning
confidence: 98%